Hints for the busy housewife (London : Health & Cleanliness Council)
1939-05 1939 1930s 50 pages : illustrations HINTS FOR THE BUSY HOUSEWIFE any food they touch, and will greatly detract from your natural and healthy enjoyment of what you eat. Many cases of typhoid fever and food poisoning have been traced to germs from bodily excretions being conveyed to food by the dirty hands of the cook. That is why it is most important to wash the hands after using the lavatory. Children should be taught this good rule as early as possible. The finger nails require regular attention. They are more easily kept clean if worn short, and are also less likely to catch in things and break. Before attending to the nails, soak the hands thoroughly well in hot soapy water and brush vigorously with a well-soaped nailbrush. Then, after drying carefully, file or cut the nails to the shape of the finger. Push back the skin round the nails with a soft towel or with the finger every time you wash your hands. This will prevent hang nails, which are sore and ugly. If your hands are inclined to become rough and chapped in the winter, remember to place them in cold water for a few seconds after having washed them thoroughly with hot water and soap. This will close the pores and make the skin less sensitive. Dry the hands and wrists very carefully. It is a good plan to keep a pot of cold cream by the side of the sink or wash-basin and rub a little well into the skin each time after the hands are washed. Many housewives think that it is impossible to prevent the hands becoming coarsened and roughened by housework, but much can be done to obviate this by caring for these two useful members in the simple ways that have been suggested. Page Thirty-four 177/5/8/1